Espaço ambiental: divulgação do meio ambiente na webrádio Porto do Capim - Sousa, Antonia Iranilde de (2016)
With environmental journalism as a practice of awareness and culture of sustainability, the present work had the objective of producing a radiojournalistic program with transmission by webrádio Porto do Capim. In this sense, the research was presented in a series of three programs on waste in the municipality of João Pessoa, addressing aspects in the context of sustainability. For this, the choice of this product was mainly motivated by the fact that radio is a popular means of communication and, therefore, suitable for broadcasting radio programs that disseminate news about the environment and can make listeners aware of sustainable practices, provoke Changes and habits of behavior and alert to a new concept of citizenship. Its webcasting Porto do Capim is effective because it is an already consolidated communication tool, having in its programming contents that dialogue with all publics, privileging, above all, the sociocultural and environmental demands of society, and comes every day, broadened its scope of action, being this tool, in the information and mobility era, a disseminating channel of knowledge, and it is shown as the best vehicle for the dissemination of the theme that is the object of this work.